2013
DOI: 10.1039/c2sc21322b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of all-benzene carbon nanocages: a junction unit of branched carbon nanotubes

Abstract: The first synthesis of an all-benzene carbon nanocage 1, which represents a junction unit of branched carbon nanotubes, has been achieved. A stepwise assembly of six L-shaped units [cis-di(p-bromophenyl) cyclohexane derivative] and two three-way units (1,3,5-triborylbenzene) by cross-coupling and homocoupling provided the unstrained cyclic precursor. Acid-mediated aromatization of cyclohexane moieties in the precursor resulted in the formation of carbon nanocage 1. Photophysical measurements and DFT studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(78 citation statements)
references
References 50 publications
0
73
0
5
Order By: Relevance
“…[74] Similar to Itamis synthesis of U-shaped units for [14]- [16]CPPs from diborylbenzene and L-shaped units,t rifurcated unit 166 was obtained by at hreefold Suzuki-Miyaura coupling of 1,3,5-triborylbenzene with L-shaped unit 59 b.N ickel-mediated dimerization of 166 provided an unstrained bicyclic precursor 167,w hose six cyclohexanem oieties were subsequently aromatized to afford the [6.6.6]carbon nanocage 163. 164 and 165).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[74] Similar to Itamis synthesis of U-shaped units for [14]- [16]CPPs from diborylbenzene and L-shaped units,t rifurcated unit 166 was obtained by at hreefold Suzuki-Miyaura coupling of 1,3,5-triborylbenzene with L-shaped unit 59 b.N ickel-mediated dimerization of 166 provided an unstrained bicyclic precursor 167,w hose six cyclohexanem oieties were subsequently aromatized to afford the [6.6.6]carbon nanocage 163. 164 and 165).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Through this synthetic route, [6.6.6]carbon nanocage (3) was successfully synthesized. 17 To synthesize smaller carbon nanorings (1 and 2), a phenylcyclohexanone derivative was chosen for the small bent unit (eq 4).…”
Section: -1 Strategy and Overviewmentioning
confidence: 99%
“…16 In 2012, we designed and proposed all-benzene carbon nanocages, three-dimensional cage-shaped conjugated hydrocarbons consisting solely of sp 2 -carbons and covalent bonds, as a new family of molecular nanocarbons (Figure 1). 17 The [n.n.n]carbon nanocages consist of three [n]paraphenylene bridges connected by two benzene-1,3,5-triyl bridgeheads. As carbon nanocages represent junction units of branched CNTs (Figure 1), the conditions we developed for CPP-to-CNT (ring-to-tube) conversion could be applied for the bottom-up synthesis of branched CNTs using carbon nanocages as templates.…”
Section: Introductionmentioning
confidence: 99%
“…While this work was ongoing, Matsui et al 40 reported on the synthesis of a p-conjugated 3D molecule that possessed a simpler bicyclic structure than 3, which is tricyclic, using a modification of the strategy they developed for CPP synthesis. However, the synthesis required long reaction steps and the final product was only obtained in a low overall yield.…”
Section: Discussionmentioning
confidence: 99%